Urgensi Kepemimpinan Transformasional dalam Mendukung Prestasi Kerja Pegawai Perpustakaan (Studi Kasus: Sekolah Menengah Atas Negeri 3 Muaro Jambi) - Kurniawati, Nila; Ramayanti, Rory (Baitul ’Ulum: Jurnal Ilmu Perpustakaan dan Informasi, 2023)
ABSTRACT This study aims to determine the transformational leadership of the librarian in supporting the work performance of librarian at SMA Negeri 3 Muaro Jambi, Jambi Province, to find out the obstacles to the head of the library in leading the library, and to find out the efforts made by the head of the library in realizing a dynamic library through transformational leadership. This study used descriptive qualitative methods, and data collection was carried out by determining the subject by using purposive sampling. Data collection techniques using observation, interviews, documentation, and data analysis. The results of this study indicate that the leadership of the librarian at SMA Negeri 3 Muaro Jambi has important aspects in transformational leadership, namely; being an ideal role model, motivating and inspiring, caring for followers, and intellectual stimulation. The head librarian’s obstacle in leading the library lies in the direct communication between the librarian and the librarian, and the second constraint is that the staff has different educational backgrounds, and the third constraint is staff behavior. Efforts made by the head of the library in obtaining a dynamic library through transformational leadership by enforcing employee discipline, providing rewards and adding Human Resources (HR).